Maricomprender la clínica de lo menor y (re)tocar el afuera de la normatividad genérico-sexual. Una entrevista epistolar con Fabrice Bourlez. - ONÍRIA, DÉBORA (Nomadías)
Epistolary interview with Fabrice Bourlez, author of Queer psicoanálisis/ Queoír el psicoanálisis (2021), performed between March and June 2022, after the workshop Deshacer el género. Psicoanálisis, (en) lo menor, implemented by Débora Oníria and Carolina Pezoa, Chilean poet and psychoanalyst who passed away last fall 2023. The interview addresses different aspects of the "clinic of the minor", a movement inside psychoanalysis that emerges in France. In the light of the above, the relationship between psychoanalysis and queer theory, the implications of philosophical thought around the question of desire, the queerization of art history, the unconscious, psychic suffering, the affirmation of difference and the conformation of a safe space as ethical principles of analytical consultation framed in the vindication of sexual and (non) reproductive rights, its political, social, clinical and intersubjective aporias are thematized.